PELAKSANAAN TERAPI RASIONAL EMOTIF DALAM MENINGKATKAN KETERAMPILAN SOSIAL PADA REMAJA AKHIR [THE IMPLEMENTATION OF EMOTIONAL RATIONAL THERAPY IN INCREASING SOCIAL SKILLS IN ADOLESCENTS] - Indifatul Anikoh; N Nurjannah (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2022)
This study aims to provide assistance to clients L in solving problems that are being faced in the form of wrong thinking patterns that make it difficult for clients to interact with other people, using rational emotive therapy (RET). In this case, rational emotive therapy is used because it emphasizes the cognitive and emotional aspects that can help clients change their thinking patterns. The method used in this research is a qualitative approach. The counseling process carried out is five sessions that discuss client problems. The results of the counseling process that the counselor has done to clients by reflecting on problems, providing motivation, giving advice and observing client activities, clients begin to open up to their surrounding environment by gradually communicating with other people and clients who decide to take part in campus organizational activities.